Recenzja monografii Kształcenie socjologów w uczelniach publicznych i niepublicznych w Polsce autorstwa Krystyny Leśniak-Moczuk - Walczak-Duraj, Danuta (Człowiek i Społeczeństwo, 2022)
The subject of the review is a monograph focusing on looking for the causes and determinants of changes taking place in the education system of sociologists in Poland. In the publication, its author presented the results of theoretical analysis and conducted empirical research. The research is in-depth and consistent in a methodological sense, and the approach to the description, diagnosis and interpretation of the most important thematic problems is balanced. The paper presents the leading trends and dynamics of educating Polish sociologists in a comparative aspect, relating to public and private universities. The cognitive and application values of the monograph are the basis for the search for solutions increasing the importance of sociological education in Poland.